依頼の丁寧度と文末音調 : 日英比較(2) - 吉村, 雅仁; 後藤, 美知子 (全国英語教育学会紀要, 1995)
This paper reports the results of an investigation into the intonational influence on politeness judgements of requesting forms in English and Japanese through a questionnaire survey. The result confirmed the hypotheses which were presented in our last article that (1) intonation has a greater influence on politeness judgements in English than in Japanese and (2) the rising tone has a tendency to be perceived as more polite than the falling tone in English, but such a tendency is not observed in Japanese. Moreover, the uniformity of the informant-group enabled us to demonstrate the relative tendency of English male/female and elder/younger group concerning the perception of intonation. The female and the younger group tended to distinguish between the rising and falling tones more clearly than the opposite group in informal situations. This tendency was not found in the Japanese group.